Impact of Previous Abdominal Surgery on Laparoscopic Cystectomy/Oophorectomy Results: A Comparative Clinical Study - W, Hazim; R, Roszaman (IIUM Medical Journal Malaysia, 2012)
Introduction: In the past, patients with previous abdominal surgery were discouraged from laparoscopic surgery because of perceived increased risk of bowel injury caused by needle and trocar insertion. However, data on the feasibility and safety of surgery of this nature is increasing. We aim to evaluate the surgical outcome of laparoscopic ovarian cystectomy/oophorectomy in previous abdominal surgery. Methods: This is a cross-sectional study with descriptive analysis of retrospective data collection from the electronic medical records of women with laparoscopic ovarian cystectomy/ oophorectomy from January 2000 until Dec 2008. Results from patients with previous abdominal surgery were compared with those of women without prior abdominal surgery. Results: Three hundred and seventeen (317) laparoscopic cystectomies/ oophorectomies were performed during the study period. 71 patients (22.5%) had previous history of abdominal surgery. Adhesions were found in 72% of patients versus 40% (p=0.001) who had previous abdominal surgery but the conversion to open surgery rate was similar (3%, p < 0.05). There was no significant difference in blood loss (134.1 ml ±18.6 vs 119.0 ml ± 9.5), operating time (107 min ± 42.0 versus 102.6 min ± 42.6) and postoperative hospital stay (1.92 days ± 1.0 vs 1.91 days ± 0.7 ). The incidence of peri-operative and post-operative complication showed no significant difference in those who had undergone previous abdominal surgery than those without prior abdominal surgery (p=0.7). The overall complication rate in this series was 0.32 %. Conclusion: Laparoscopic cystectomy/ oophorectomy in the previous abdominal surgery is safe with no increase in morbidity.